Transcriptomic signatures of ash (Fraxinus spp.) phloem. - Xiaodong Bai; Loren Rivera-Vega; Praveen Mamidala; Pierluigi Bonello; Daniel A Herms; Omprakash Mittapalli (PLoS ONE, 2011)
Background Ash (Fraxinus spp.) is a dominant tree species throughout urban and forested landscapes of North America (NA). The rapid invasion of NA by emerald ash borer (Agrilus planipennis), a wood-boring beetle endemic to Eastern Asia, has resulted in the death of millions of ash trees and threatens billions more. Larvae feed primarily on phloem tissue, which girdles and kills the tree. While NA ash species including black (F. nigra), green (F. pennsylvannica) and white (F. americana) are highly susceptible, the Asian species Manchurian ash (F. mandshurica) is resistant to A. planipennis perhaps due to their co-evolutionary history. Little is known about the molecular genetics of ash. Hence, we undertook a functional genomics approach to identify the repertoire of genes expressed in ash phloem. Methodology and principal findings Using 454 pyrosequencing we obtained 58,673 high quality ash sequences from pooled phloem samples of green, white, black, blue and Manchurian ash. Intriguingly, 45% of the deduced proteins were not significantly similar to any sequences in the GenBank non-redundant database. KEGG analysis of the ash sequences revealed a high occurrence of defense related genes. Expression analysis of early regulators potentially involved in plant defense (i.e. transcription factors, calcium dependent protein kinases and a lipoxygenase 3) revealed higher mRNA levels in resistant ash compared to susceptible ash species. Lastly, we predicted a total of 1,272 single nucleotide polymorphisms and 980 microsatellite loci, among which seven microsatellite loci showed polymorphism between different ash species. Conclusions and significance The current transcriptomic data provide an invaluable resource for understanding the genetic make-up of ash phloem, the target tissue of A. planipennis. These data along with future functional studies could lead to the identification/characterization of defense genes involved in resistance of ash to A. planipennis, and in future ash breeding programs for marker development.